2001
DOI: 10.1161/hs1201.99512
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Expression Is Related to Hemorrhagic Transformation After Cardioembolic Stroke

Abstract: Background and Purpose-In animal models of cerebral ischemia, matrix metalloproteinase (MMP) expression was significantly increased and related to blood-brain barrier disruption, edema formation, and hemorrhagic transformation (HT). MMP inhibitors reduce HT after embolic ischemia in tissue-type plasminogen activator-treated animals. We aimed to determine the relationship between MMPs and HT after human ischemic stroke. Methods-Serial MMP-2 and MMP-9 determinations were performed by means of ELISA in 39 cardioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(234 citation statements)
references
References 34 publications
8
217
1
8
Order By: Relevance
“…Moreover, to our knowledge, only a few preclinical studies have been conducted to assess the effects of the pharmacological modulation of hematoma growth 6. On the other hand, MMPs have been implicated in brain injury after ICH in animal models and in humans12, 13, 26; in particular, blood MMP‐9 concentration has been associated with hemorrhagic transformation 27. Rapid MMP upregulation after ICH has been proposed to cause neurovascular matrix degradation, proteolyzing the basal lamina around blood vessels and disrupting endothelial tight junctions, leading to edema, hemorrhage, and cell death 13.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to our knowledge, only a few preclinical studies have been conducted to assess the effects of the pharmacological modulation of hematoma growth 6. On the other hand, MMPs have been implicated in brain injury after ICH in animal models and in humans12, 13, 26; in particular, blood MMP‐9 concentration has been associated with hemorrhagic transformation 27. Rapid MMP upregulation after ICH has been proposed to cause neurovascular matrix degradation, proteolyzing the basal lamina around blood vessels and disrupting endothelial tight junctions, leading to edema, hemorrhage, and cell death 13.…”
Section: Discussionmentioning
confidence: 99%
“…Those with severe strokes had significantly higher levels of MMP-9 at baseline, and the elevated levels persisted for 48 h (Montaner et al, 2001a). When hemorrhagic transformation or parenchymal hemorrhages were present, the highest levels of MMP-9 were found in those patients with late hemorrhagic transformation (Montaner et al, 2001b). Studies in nonhuman primates have shown that the levels of MMP-9 were associated with hemorrhagic transformation, while MMP-2 correlated with neuronal injury (Heo et al, 1999).…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 99%
“…Once released upon neutrophil activation, MMP-9 breaks down the extracellular matrix, leading to vascular dilation/ weakening. 24,[26][27][28][29][30][31][32][33][34][35][36][37] Using substrate zymography, Hashimoto et al 30 determined that the expression of total MMP-9, pro-MMP-9, and active MMP-9 was significantly increased in AVMs in comparison to control brain tissue. The levels of MMP inhibitors, tissue inhibitor of metalloproteinase 1 (TIMP-1), and TIMP-3, were also increased in AVMs, although to a lesser extent than MMP-9.…”
Section: Vascular Instabilitymentioning
confidence: 99%